2000
DOI: 10.1348/014466600164363
|View full text |Cite
|
Sign up to set email alerts
|

Essentialist beliefs about social categories

Abstract: This study examines beliefs about the ontological status of social categories, asking whether their members are understood to share fixed, inhering essences or natures. Forty social categories were rated on nine elements of essentialism. These elements formed two independent dimensions, representing the degrees to which categories are understood as natural kinds and as coherent entities with inhering cores ('entitativity' or reification), respectively. Reification was negatively associated with categories' eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
989
6
26

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 807 publications
(1,072 citation statements)
references
References 17 publications
31
989
6
26
Order By: Relevance
“…Of course, not all essentializing is good, as in the well-documented tendencies to think of the essence of an out-group as a category, e.g. 'the essence of Arab immigrants' (Haslam, Rothschild, & Ernst, 2000. In contrast, our studies show that asking people to think about the essence of an individual person, e.g.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Of course, not all essentializing is good, as in the well-documented tendencies to think of the essence of an out-group as a category, e.g. 'the essence of Arab immigrants' (Haslam, Rothschild, & Ernst, 2000. In contrast, our studies show that asking people to think about the essence of an individual person, e.g.…”
Section: Discussioncontrasting
confidence: 61%
“…Yet at first glance it would appear that the good true self bias has no chance of holding for out-group members, since aside from the strength of intergroup bias, it is well documented that people tend to think of the essence of an out-group as a negative category, e.g., 'the essence of Arab immigrants' (Haslam, Rothschild, & Ernst, 2000. Here we emphasize that the good true self bias is one that falls out of reasoning about the essence of an individual person.…”
Section: The Good True Selfmentioning
confidence: 99%
“…As described above, Haslam et al (2000) have demonstrated that adults' essentialist beliefs embody the components of naturalness and cohesiveness. However, most studies of the development of essentialist thinking utilize a single measure of such thinking.…”
Section: Future Directionsmentioning
confidence: 77%
“…Diesendruck, 2013;Leslie, Cimpian, Meyer & Freeland, 2015). In this paper we examine the development of essentialist thinking about socially important religion categoriesCatholic and Protestant-in Northern Ireland, with particular attention toward how school and national context may contribute to differences in the use of social categories to guide inferences.Essentialist thinking about social categories in particular has been widely investigated (e.g., Haslam, Rothschild & Ernst, 2000;Hirschfeld, 1996;Rothbart & Taylor, 1992; Yzerbyt, Corneille & Estrada, 2001), and there have been a variety of suggestions about its causes. One possibility is that it may represent an application of the same fundamental conceptual machinery that we use for thinking about natural kinds to the critical task of navigating our complex social environment (Gil-White, 2001).…”
mentioning
confidence: 99%
“…No que concerne às crenças essencialistas relativas exclusivamente aos homossexuais, Hegarty e Pratto (2001) identificaram duas dimensões organizadoras destas crenças sobre a homossexualidade (ver também Haslam, Rothschild, & Ernst, 2000): imutabilidade -a crença de que a homossexualidade é biologicamente determinada, fixada no início da vida e difícil de mudança; e fundamentalismo -a crença na distintividade dos homossexuais relativamente aos heterossexuais. Posteriormente, Haslam e Levy (2006) identificaram uma terceira dimensão: universalismo -definida pela crença de que a homossexualidade é historicamente e culturalmente determinada.…”
Section: Representações Sobre a Natureza Da Homossexualidade E Preconunclassified